2006
DOI: 10.1248/bpb.29.846
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Acebutolol through Rabbit Corneal Epithelium

Abstract: In ophthalmic pharmacotherapy, the cornea is considered to be a major pathway for ocular permeation of topically applied drugs.1,2) The cornea, however, is impermeable to hydrophilic compounds because of a poor paracellular route due to the epithelial tight junctions. 3,4) Passive diffusion across the lipid cell membrane primarily contributes to the penetration of most ophthalmic drugs through the intact cornea. Many drugs had an almost parabolic relationship between the corneal permeability and the drug lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…P-gp is a major drug efflux pump that is expressed on corneal epithelium (Dey et al, 2003; Verstraelen and Reichl, 2013). This efflux pump has been demonstrated to play an active role in limiting corneal permeability of various therapeutic agents (Dey et al, 2004; Dey et al, 2003; Hariharan et al, 2009a; Katragadda et al, 2006; Kawazu et al, 2006). Extensive efflux of therapeutic agents at corneal epithelium may result in poor drug efficacy and emergence of resistance.…”
Section: Resultsmentioning
confidence: 99%
“…P-gp is a major drug efflux pump that is expressed on corneal epithelium (Dey et al, 2003; Verstraelen and Reichl, 2013). This efflux pump has been demonstrated to play an active role in limiting corneal permeability of various therapeutic agents (Dey et al, 2004; Dey et al, 2003; Hariharan et al, 2009a; Katragadda et al, 2006; Kawazu et al, 2006). Extensive efflux of therapeutic agents at corneal epithelium may result in poor drug efficacy and emergence of resistance.…”
Section: Resultsmentioning
confidence: 99%
“…The only compound that we excluded from this study was acebutolol, whose corneal permeability has been reported by two sources included in this study (4,18). Previously, it has been identified as an outlier in modeling studies (12,13), and, recently, acebutolol has been reported to be actively transported by MDR-1 in rabbit cornea (38).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Pgp-mediated efflux may play an important role in ocular disposition of therapeutic agents following topical administration. Pgp may be involved in limiting the transcorneal permeability of various therapeutic agents (6,8,14,27,42). Hence, evasion of this efflux pump at corneal epithelium might significantly improve transcorneal drug permeation and accumulation in anterior ocular tissues following topical administration.…”
Section: Cellular Uptake Studiesmentioning
confidence: 99%